Dos expresiones para la esperanza de una variable aleatoria (2015)
In the basic texts, the deﬁnition of the expected value of a random variable is diﬀerent from the deﬁnition given in a probability course based on the theory of measure. In this manuscript it is shown why both deﬁnitions are in fact equivalent.